Identifying the Real Minority Carrier Lifetime in Nonideal Semiconductors: A Case Study of Kesterite Materials. Issue 18 (23rd May 2017) - Hages, Charles J.; Redinger, Alex; Levcenko, Sergiu; Hempel, Hannes; Koeper, Mark J.; Agrawal, Rakesh; Greiner, Dieter; Kaufmann, Christian A.; Unold, Thomas
Abstract : Time‐resolved photoluminescence (TRPL) is a powerful characterization technique to study carrier dynamics and quantify absorber quality in semiconductors. The minority carrier lifetime, which is critically important for high‐performance solar cells, is often derived from TRPL analysis. However, here it is shown that various nonideal absorber properties can dominate the TRPL signal making reliable extraction of the minority carrier lifetime not possible. Through high‐resolution intensity‐, temperature‐, voltage‐dependent, and spectrally resolved TRPL measurements on absorbers and devices it is shown that photoluminescence (PL) decay times for kesterite materials are dominated by minority carrier detrapping. Therefore, PL decay times do not correspond to the minority carrier lifetime for these materials. The lifetimes measured here are on the order of hundreds of picoseconds in contrast to the nanosecond lifetimes suggested by the decay curves. These results are supported with additional measurements, device simulation, and comparison with recombination limited PL decays measured on Cu(In, Ga)Se2 . The kesterite material system is used as a case study to demonstrate the general analysis of TRPL data in the limit of various measurement conditions and nonideal absorber properties. The data indicate that the current bottleneck for kesterite solar cells is the minority carrier lifetime. Abstract : Minority carrier lifetimes are often overestimated for kesterite materials from time‐resolved photoluminescence (TRPL) due to complex charge carrier dynamics in this material system. Here, it is shown that detrapping processes dominate the photoluminescence decay for Cu2 ZnSnSe4 and Cu2 ZnSn(S, Se)4 . Minority carrier lifetimes ≤500 ps are estimated from TRPL, device simulation, and additional measurements demonstrating a significant performance limitation.